Pemanfaatan kurikulum pondok pesantren dalam membentuk karakter santri - Salindry, Agesta Eka; Afriantoni; Muhammad Win (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
The curriculum of education in Islamic boarding schools has a very important contribution as an effort to develop an education system based on local wisdom or to shape the character of students. The development of the curriculum of Islamic boarding schools is expected to be able to provide a distinctive color in the dynamics of society. Qualitative research uses an approach, narrative, literature review which is sourced from various sources that discuss education, especially Islamic boarding schools. Data collection techniques through document checking and confirmation through deep observation with students, and ustadz and his staff for samples. Data analysis uses inductive techniques, starting with grouping data according to theme, and giving meaning to each new section, then concluded descriptively. The results of the study show that the utilization or development of the Islamic boarding school curriculum still maintains the characteristics, characteristics and character of students for provisions in the wider community. Abstrak Kurikulum Pendidikan di pondok pesantren memiliki kontribusi yang sangat penting sebagai Upaya untuk pengembangan sistem Pendidikan yang berbasis kearifan lokal atau membentuk karakter santri. Pengembangan kurikulum pondok pesantren ini diharapkan mampu memberi warna khas dalam dinamika bermasyarakat. Penelitian kualitatif menggunakan dengan cara pendekatan, narrative literature review yang bersumber pada berbagai yang membahas tentang Pendidikan khususnya pesantren. Teknik pengumpulan data melalui pengecekan dokumen dan konfirmasi melalui observasi secara random dengan santri, dan ustaz berserta jajarannya untuk sampel. Analisis data menggunakan Teknik induktif, diawali dalam mengelompokkan data sesuai tema, dan memberikan makna setiap bagian baru disimpulkan secara deskriptif. Hasil penelitian menunjukkan bahwa, pemanfaatan atau pengembangan kurikulum pondok pesantren tetap mempertahankan corak, khas dan karakter santri untuk bekal di Masyarakat luas.